An investigation of the stirring duration effect on synthesized graphene oxide for dye-sensitized solar cells - Yau X.H.; Low F.W.; Khe C.S.; Lai C.W.; Tiong S.; Amin N. (Public Library of Science, 2023)
graphene oxide; nanocomposite; oxygen; titanium dioxide nanoparticle; coloring agent; graphene oxide; graphite; absorption parameters; Article; electron transport; energy dispersive X ray spectroscopy; field emission scanning electron microscopy; Fourier transform infrared spectroscopy; Hummer method; impedance spectroscopy; oxidation; Raman spectrometry; reduction (chemistry); synthesis; time; X ray diffraction; chemistry; power supply; solar energy; Coloring Agents; Electric Power Supplies; Graphite; Solar Energy